2019
DOI: 10.1016/j.jbo.2018.100215
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of skeletal-related events among multiple myeloma patients in the United States at oncology clinics: Observations from real-world data

Abstract: Skeletal-related events (SREs) are common bone complications in multiple myeloma (MM). However, there are few real-world reports of their incidence. In this study, a database of oncology electronic health records was linked to administrative claims data. Patients identified were aged ≥18 years and newly diagnosed with MM, had ≥1 clinic visit within 1 month of diagnosis, and ≥1 year of follow-up after diagnosis. The study period was January 1, 2011 to December 31, 2016. 343 patients were included, 35% of whom h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
6
28
0
Order By: Relevance
“…We also found that approximately half of bone complications occurred before initiation of first-line treatment (over a mean duration of 2.3 months); however, some of these may have already been present at diagnosis. Results from other studies suggest that most bone complications occur within the first year after MM diagnosis [10,16]; for example, Kim et al reported that 68% of bone complications occurred during this period [16]. In a recent randomized controlled trial in patients with NDMM (N = 1718), 60% of first on-study bone complications were experienced during the initial 3 months and 81% during the initial 6 months of the study [10].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We also found that approximately half of bone complications occurred before initiation of first-line treatment (over a mean duration of 2.3 months); however, some of these may have already been present at diagnosis. Results from other studies suggest that most bone complications occur within the first year after MM diagnosis [10,16]; for example, Kim et al reported that 68% of bone complications occurred during this period [16]. In a recent randomized controlled trial in patients with NDMM (N = 1718), 60% of first on-study bone complications were experienced during the initial 3 months and 81% during the initial 6 months of the study [10].…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our findings, Nash Smyth et al estimated that, among patients who experienced at least one bone complication, 50% had one, 26% had two and 24% had at least three bone complications [17]. Furthermore, a retrospective US database analysis by Kim et al (N = 343) found that the incidence of bone complications 1 year after MM diagnosis for patients with a prior history of bone complications was 103 per 100 person-years compared with 16 per 100 person-years for individuals with no prior history [16]. The incidence of bone lesions was not recorded throughout our study, so it was not possible to establish the extent to which new bone complications were associated with changes in the burden of myeloma bone disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It leads to serious complications and/or skeletal-related events (SREs), which include fracture, compression of the spinal cord, hypercalcemia, and the need for further surgical treatment or radiation therapy. SREs not only decrease the quality of life as a result of pain, emotional distress, and treatment procedures, but also affect the survival of MM patients [6,[8][9][10]. Therefore, knowledge of myeloma bone lesions for further disease management is warranted.…”
Section: Introductionmentioning
confidence: 99%